Vortex beam manipulation through a tunable plasma-ferrite metamaterial - Davod Nobahar (Nature Portfolio, 2021)
Abstract This paper is devoted to the study of vortex beam transmission from an adjustable magnetized plasma-ferrite structure with negative refraction index. We use the angular spectral expansion technique together with the $$4× 4$$ 4 × 4 matrix method to find out the transmitted intensity and phase profiles of incoming Laguerre-Gaussian beam. Based on numerical analysis we demonstrate that high transparency and large amount of Faraday rotation in the proximity of resonance frequency region, reverse rotation of spiral wave front, and side-band modes generation during propagation are the remarkable features of our proposed structure. These controllable properties of plasma-ferrite metamaterials via external static magnetic field and other structure parameters provide novel facilities for manipulating intensity and phase profiles of vortex radiation in transmission through the material. It is expected that the results of this work will be beneficial to develop active magneto-optical devices, orbital angular momentum based applications, and wavefront engineering.